PARTISIPASI ORANGTUA TERHADAP PENDIDIKAN ANAK USIA DINI: SURVEI PADA KELOMPOK BERMAIN DI KOTA YOGYAKARTA - Rosdiana, Afia (JIV-Jurnal Ilmiah Visi, 2006)
This research was aimed to investigate the level of parents’ participation, expectations and comprehensions of early childhood education. It was also aimed to know the direct or indirect effects of parents’ social-economic status, environment, expectations and comprehensions of early childhood education on the level of parents’ participation on early childhood education. The population of this research was all the parents who enrolled their children to the pre-school in Yogyakarta The descriptive analysis result shows that the level of parents’ participations and expectations is in the high category. Meanwhile parents’ comprehension of early childhood education concept is in the medium category. Since, the level of parents’ participation in early childhood education was highly affected by parents’ comprehensions, it can be stated that to raise the level of participations of parents in early childhood education, it is necessary to raise the parents’ comprehensions as well. Besides the efforts of the early childhood education institution to increase parents’ comprehensions, the government can also do this through parallel policies so that there is a harmony in parenting patterns.